2018
DOI: 10.1002/etep.2803
|View full text |Cite
|
Sign up to set email alerts
|

Ant lion optimizer versus particle swarm and artificial immune system for economical and eco‐friendly power system operation

Abstract: Summary Economic load dispatch (ELD) became recently a mandatory tool for reliable and economic power system operation. ELD improves the security of the power supply while minimizing the generation costs. Daily load curve imposes conflicting requirements on ELD scheme, such as fulfilling demand during peak periods while limiting the cost. Demand response (DR) is an intelligent approach that ensures load demand fulfillment without introducing additional costs. DR allows shifting the electricity consumption to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In Case 1, taking 10 units in a power plant (Basu 2016) as an example, the coal consumption characteristic parameters of the unit and the upper and lower limits of the unit load are shown in the following Table 1: In the case of a 10-unit medium-sized power plant, this paper uses the improved crisscross hybrid bacterial foraging algorithm (ICSBFO), the crisscross algorithm (CSO) (Meng et al, 2015), the bacterial foraging algorithm (BFO), and the particle swarm algorithm (PSO) (Hatata and Hafez 2019) to solve the 10-unit load optimization distribution model of a medium-sized power plant. Since different unit parameters and valve point effect parameters greatly influence the results of unit load economic dispatch, this paper uses the methods proposed by them in their respective articles to simulate the unit parameters of the same case.…”
Section: Case Of 10 Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Case 1, taking 10 units in a power plant (Basu 2016) as an example, the coal consumption characteristic parameters of the unit and the upper and lower limits of the unit load are shown in the following Table 1: In the case of a 10-unit medium-sized power plant, this paper uses the improved crisscross hybrid bacterial foraging algorithm (ICSBFO), the crisscross algorithm (CSO) (Meng et al, 2015), the bacterial foraging algorithm (BFO), and the particle swarm algorithm (PSO) (Hatata and Hafez 2019) to solve the 10-unit load optimization distribution model of a medium-sized power plant. Since different unit parameters and valve point effect parameters greatly influence the results of unit load economic dispatch, this paper uses the methods proposed by them in their respective articles to simulate the unit parameters of the same case.…”
Section: Case Of 10 Unitsmentioning
confidence: 99%
“…The other group of intelligent algorithms is also gradually being developed is applied to the ELD problems. (Hatata and Hafez 2019) is optimized by the ant lion algorithm (ALO) compared with the PSO algorithm and artificial immune system (AIS). The results found that the ALO in dealing with ELD has higher efficiency and convergence precision.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in [157], [158] authors proposed an approach to solve optimal reactive power dispatch (ORPD). Also, Alazemi and Hatata [159] Considered Demand Response as a Visual Power Plant to solve the Optimum Economic Dispatch problem.. Also, Hatata and Hafez [160] employed ALO, PSO, and AIS in solving ELDP problem by trying to minimize cost, emission levels, and system losses. In [159], another attamp to solve economic dispatch with respect to demand response as a visual power.…”
Section: ) Load Dispatchmentioning
confidence: 99%